PROFITABILITY OF COMMERCIAL BROILER CHICKEN UNDER DIFFERENT LIGHT REGIME (Indian Journal of Animal Production and Management, 2015)
The study was conducted on 200 commercial broiler chickens (Vb-100 strain) under standard managemental conditions to find out the livability and relative economics of commercial broiler chicken reared under coloured light, continuous light and intermittent light regime in deep litter system. After seven days of brooding broiler chicks were divided into 8 groups according to different light regime. 100% livability was recorded for all the groups from 2nd to 6th week. Better performance was observed in blue followed by green, red and white coloured light. Highest profit was derived from birds kept under blue light (18L+6D) and lowest profit was derived from birds kept under white light (23L+1D).
Keywords: Broiler chicken; light; livability; economics